Evaluation of Tunnel Surrounding Rock Quality Based on Composite Weight Grey Relational Analysis - JIANG Pengfei; DU Faxing; WANG Xuerong; ZHOU Jingtao (Renmin Zhujiang)
In order to accurately evaluate the stability of tunnel surrounding rock,and reduce the risk in the process of excavation,this paper selects the uniaxial saturated compressive strength of rock,the integrity coefficient of rock mass,the groundwater condition and the state of structure plane as the evaluation indexes of surrounding rock,establishes the combined weight calculation method based on entropy weight method and analytic hierarchy process,constructs the evaluation model for tunnel surrounding rock quality by the grey relational analysis,and verifies the model by the improved BQ method,taking Xishanying tunnel in Yunnan Province as an example.The comparison shows that the evaluation results of grey relational analysis model is highly consistent with that of the improved BQ method.The evaluation model is highly feasible and reliable,which can provide reference for the quality evaluation of surrounding rock.